Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(=\frac{7-4\sqrt{3}+7+4\sqrt{3}}{\left(7+4\sqrt{3}\right)\left(7-4\sqrt{3}\right)}=\frac{14}{49-48}=14\)
b) \(=\frac{15\left(\sqrt{6}-1\right)}{\left(\sqrt{6}+1\right)\left(\sqrt{6}-1\right)}-\frac{5\sqrt{6}}{5}+\frac{4\sqrt{3}-12\sqrt{2}}{\sqrt{6}\left(\sqrt{3}-\sqrt{2}\right)}\)
\(\frac{\sqrt{9-4\sqrt{5}}}{2-\sqrt{5}}\)
= \(\frac{\sqrt{2^2-2\sqrt{5}2+\sqrt{5^2}}}{2-\sqrt{5}}\)
= \(\frac{\sqrt{\left(2-\sqrt{5}\right)^2}}{2-\sqrt{5}}\)
= \(\frac{\sqrt{5}-2}{2-\sqrt{5}}\)
= -1
Chúc bạn làm bài tốt :)
\(A=\frac{1}{\sqrt{11-2\sqrt{30}}}-\frac{3}{\sqrt{7-2\sqrt{10}}}+\frac{4}{\sqrt{8+4\sqrt{3}}}\)
\(=\frac{1}{\sqrt{6-2.\sqrt{6}.\sqrt{5}+5}}-\frac{3}{\sqrt{5-2.\sqrt{5}.\sqrt{2}+2}}+\frac{2}{\sqrt{4+2\sqrt{3}}}\)
\(=\frac{1}{\sqrt{\left(\sqrt{6}-\sqrt{5}\right)^2}}-\frac{3}{\sqrt{\left(\sqrt{5}-\sqrt{2}\right)^2}}+\frac{2}{\sqrt{\left(\sqrt{3}+1\right)^2}}\)
\(=\frac{1}{\sqrt{6}-\sqrt{5}}-\frac{3}{\sqrt{5}-\sqrt{2}}+\frac{2}{\sqrt{3}+1}\)
\(=\frac{6-5}{\sqrt{6}-\sqrt{5}}-\frac{5-2}{\sqrt{5}-\sqrt{2}}+\frac{3-1}{\sqrt{3}+1}\)
\(=\frac{\left(\sqrt{6}-\sqrt{5}\right)\left(\sqrt{6}+\sqrt{5}\right)}{\sqrt{6}-\sqrt{5}}-\frac{\left(\sqrt{5}-\sqrt{2}\right)\left(\sqrt{5}+\sqrt{2}\right)}{\sqrt{5}-\sqrt{2}}+\frac{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}{\sqrt{3}+1}\)
\(=\sqrt{6}+\sqrt{5}-\sqrt{5}+\sqrt{2}+\sqrt{3}+1=\sqrt{6}+\sqrt{2}+\sqrt{3}+1\)
\(=\sqrt{2}\left(\sqrt{3}+1\right)+\sqrt{3}+1=\left(\sqrt{3}+1\right)\left(\sqrt{2}+1\right)\)
\(\frac{2}{4\sqrt{3}-7}+\frac{2}{4\sqrt{3}+7}\)
\(=-14-8\sqrt{3}+14-8\sqrt{3}\)
\(=-16\sqrt{3}\)